1987
DOI: 10.1002/eji.1830170308
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of T cells reactive with Mycobacterium tuberculosis organisms and specific for the recombinant mycobacterial 64‐kDa protein

Abstract: The major goal of the present study was to develop a limiting dilution system for the enumeration of T cells which respond to mycobacterial antigens. Purified T cells from M. tuberculosis-immune mice were restimulated with mycobacterial antigens and accessory cells, and after 4 days expanded with antigen, accessory cells and T cell growth factor. After another 3 days, proliferative responses were determined. Similar cultures performed without antigen served as controls. Limiting dilution analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(112 citation statements)
references
References 17 publications
2
107
0
Order By: Relevance
“…An interesting property of heatshock proteins (HSPs) is their highly immunogenic nature (24). To investigate the nature of the response stimulated by BiP, DBA/1 mice were immunized subcutaneously with 200 g BiP either solubilized in PBS or emulsified in IFA.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting property of heatshock proteins (HSPs) is their highly immunogenic nature (24). To investigate the nature of the response stimulated by BiP, DBA/1 mice were immunized subcutaneously with 200 g BiP either solubilized in PBS or emulsified in IFA.…”
Section: Resultsmentioning
confidence: 99%
“…This approach was considered to be particularly promising for tumors in which dominant antigens are poorly characterized as is the case of HNSCC. Second, considering that Hsp65 is an immunodominant antigen in mycobacteria, 36 the expression of this foreign protein by tumor cells in the context of HLA class I molecules could lead to breakdown of the tolerogenic environment found in cancer patients. As with any new type of therapy, there are important safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it stimulates the proliferation of T cells in immune mice, suggesting that it is likely to be involved in the development of cellmediated immunity (Kaufmann et al, 1987). In contrast, Willem et al (1985) suggested that arthritis was induced by a T-cell clone which recognized an epitope on the mycobacterial 65 kDa antigen.…”
Section: Discussionmentioning
confidence: 99%